Impact of blade structural and aerodynamic uncertainties on wind turbine loads. Issue 6 (3rd February 2022) - Gonzaga, Paulo; Toft, Henrik; Worden, Keith; Dervilis, Nikolaos; Bernhammer, Lars; Stevanovic, Nevena; Gonzales, Alejandro
Abstract: Offshore wind power has been in the spotlight among renewable energy sources. The current trends of increased power ratings and longer blades come together with the aim to reduce energy costs by design optimisation. The standard approach to deal with uncertainties in wind‐turbine design has been by the use of characteristic values and safety factors. This paper focusses on modelling the effect of structural and aerodynamic uncertainties in blades. First, the uncertainties in laminate properties are characterised and propagated in a blade structural model by means of a Monte Carlo simulation. Wind tunnel measurement data are then used to define the variability in lift and drag coefficients for both clean and rough aerofoil behaviour, which is then used to extrapolate rough behaviours throughout the blade. A stochastic spatial interpolation parameter is used to define the evolution of the degradation level. The combined effect and the variance contribution of these two uncertainty sources in turbine loads is finally defined by aeroelastic turbine simulation. This research aims to provide a framework to deal with uncertainties in wind‐turbine blade design and understand their effects in turbine behaviour.